PERSEPSI MAHASISWA TERHADAP KUALITAS PELAYANAN AKADEMIK DI MASA PANDEMI COVID-19 - chairiyaton chairiyaton; Nabila Hilmy Zhafira; Yenny Ertika (universitas teuku umar, 2020)
This study aims to determine students' perceptions of the quality of academic services during the Covid-19 pandemic at the Faculty of Economics, Teuku Umar University. To measure the quality of service, researchers used a descriptive method. Assessment of service quality is reflected in students' perceptions based on five dimensions of service quality evaluation according to Kotler (2007), namely the dimensions of reliability, responsiveness, assurance, empathy and tangible dimensions. The population used in this study were all students of the UTU Faculty of Economics consisting of three study programs, namely Development Economics, Management, and Accounting. The sampling technique was proportional simple random sampling with a sample size of 15 percent of the total population. The sampling technique uses an online questionnaire. The reliability test used the Cronbach Alpha correlation formula, while the data analysis used descriptive statistics with the SPSS application. The results obtained from the analysis of each of the variables of reliability, assurance, empathy and tangible during the Covic-19 pandemic as a whole the respondents perceived it was good, but for the responsiveness dimension, there were four items in sufficient value for the other three items, the responsiveness dimension was the same as four. Another dimension where students perceive the quality of academic services at the Faculty of Economics, Teuku Umar University during the Covid-19 pandemic is good.Keywords: service quality, student perceptions